TMEM106B Puncta Is Increased in Multiple Sclerosis Plaques, and Reduced Protein in Mice Results in Delayed Lipid Clearance Following CNS Injury - Bridget Shafit-Zagardo; Simone Sidoli; James E. Goldman; Juwen C. DuBois; John R. Corboy; Stephen M. Strittmatter; Hillary Guzik; Ukuemi Edema; Anita G. Arackal; Yair M. Botbol; Emilio Merheb; Rashed M. Nagra; et al. (Cells, 2023)
During inflammatory, demyelinating diseases such as multiple sclerosis (MS), inflammation and axonal damage are prevalent early in the course. Axonal damage includes swelling, defects in transport, and failure to clear damaged intracellular proteins, all of which affect recovery and compromise neuronal integrity. The clearance of damaged cell components is important to maintain normal turnover and restore homeostasis. In this study, we used mass spectrometry to identify insoluble proteins within high-speed/mercaptoethanol/sarcosyl-insoluble pellets from purified white matter plaques isolated from the brains of individuals with relapsing–remitting MS (RRMS). We determined that the transmembrane protein 106B (TMEM106B), normally lysosome-associated, is insoluble in RRMS plaques relative to normal-appearing white matter from individuals with Alzheimer’s disease and non-neurologic controls. Relative to wild-type mice, hypomorphic mice with a reduction in TMEM106B have increased axonal damage and lipid droplet accumulation in the spinal cord following myelin-oligodendrocyte-glycoprotein-induced experimental autoimmune encephalomyelitis. Additionally, the corpora callosa from cuprizone-challenged hypomorphic mice fail to clear lipid droplets efficiently during remyelination, suggesting that when TMEM106B is compromised, protein and lipid clearance by the lysosome is delayed. As TMEM106B contains putative lipid- and LC3-binding sites, further exploration of these sites is warranted.